PANGGILAN ILAHI BERDASARKAN YEREMIA 1:5 DAN DAMPAKNYA PADA PENGEMBANGAN DEDIKASI GURU DALAM MENGAJAR PESERTA DIDIK - Suryowati Wang; Elfan Putra Laia; Jerni Hati Waruwu (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2023)
Abstract: This study aims to explore and understand the meaning of divine calling in the context of Christian education and identify its impact on the development of teacher dedication in carrying out teaching assignments. This study uses a qualitative method with a literature study approach, involving analysis of various related literature sources. In the context of the Christian life, the divine calling has deep significance. Verse Jeremiah 1:5 becomes the central interpretation in this study, where divine calling refers to the special assignments given by God to individuals He calls. The call denotes a special election by God prior to the birth of the individual. Although the divine call applies to everyone, not everyone accepts or follows it. This study highlights some of the challenges faced in teachers' understanding and awareness of the meaning of divine calling in the context of Christian education. Some of the problems that arise include the teacher's lack of dedication in carrying out teaching duties, low motivation and commitment in carrying out vocations, lack of awareness of moral and ethical responsibilities as a Christian teacher, and deficiencies in self-development and skills improvement as a teacher. Data analysis reveals that understanding the meaning of divine calling can be a strong foundation in developing a teacher's dedication in carrying out teaching assignments. Teachers who are aware of the divine calling will voluntarily gain high dedication in carrying out their ministry as God's servants. The high dedication of a teacher who understands divine calling can also have a positive influence on students, motivate them in the learning process, and help them develop a deeper relationship with God.